2016
DOI: 10.1093/rheumatology/kew288
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of endothelial progenitor cells is associated with the type I IFN pathway in patients with polymyositis and dermatomyositis

Abstract: Objective. Alterations in phenotype and function of endothelial progenitor cells (EPCs) have been associated with poor vascular outcomes and impaired vascular repair in various conditions. Our hypothesis was that patients with PM and DM have dysregulation of EPCs driven by type I IFN and IL-18 similar to other autoimmune diseases.Methods. Quantification of circulating EPCs was performed by flow cytometry in patients with PM/DM and matched healthy controls. The ability of EPCs to differentiate into mature endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Gene expression was normalized to that of β‐actin, relative gene expression to normal controls was calculated by the comparative threshold cycle (C t ) method, and fold change was expressed as 2ΔΔnormalCnormalt . IFN scores were calculated as previously described for IFI44 , MXA , and PRKR . Briefly, the mean fold change in samples from healthy control subjects was calculated, and the SLE IFN gene score was calculated as (SLE [gene] fold change – control [mean] fold change)/SD control.…”
Section: Methodsmentioning
confidence: 99%
“…Gene expression was normalized to that of β‐actin, relative gene expression to normal controls was calculated by the comparative threshold cycle (C t ) method, and fold change was expressed as 2ΔΔnormalCnormalt . IFN scores were calculated as previously described for IFI44 , MXA , and PRKR . Briefly, the mean fold change in samples from healthy control subjects was calculated, and the SLE IFN gene score was calculated as (SLE [gene] fold change – control [mean] fold change)/SD control.…”
Section: Methodsmentioning
confidence: 99%
“…RNA-10a, a master regulator of proinflammatory cytokines via the NFkB pathway, also controls vascular system components (69). Studies of endothelial cells from adults with DM or PM showed a decrease in PM only, not in DM (70). Similarly, the number of endothelial precursor cells were normal in children with JDM (71), providing evidence that production of the endothelial cells is not the problem in JDM.…”
Section: Childhood and Adult Onset Dermatomyositis Have Differing Feamentioning
confidence: 99%
“…Patients with systemic lupus erythematosus (SLE) have an elevated vascular risk due to an early onset of atherosclerosis, which appears to be independent of traditional CVD risk factors and associated with an altered interferon-α (IFNα) signaling pathway. It has been shown that IFNα alters the balance between endothelial cell apoptosis and vascular repair which is governed by both ECFCs and MACs ( 71 , 72 ). When focusing on CD34 + cells, it becomes clear that the majority of studies find decreased levels of circulating MACs in SLE patients ( 68 ).…”
Section: Progenitor Cell Impairments In Inflammatory Rheumatic Diseasmentioning
confidence: 99%